Recursos líticos, aprovisionamiento y aspectos temporales de fuentes de abastecimiento en Amaicha del Valle, Tucumán, Argentina (Comechingonia. Revista de Arqueología, 2011)
This paper addresses the procurement of lithic raw materials and chronological aspects of procurement sources in the broad area within which the archaeological site Planchada La Puntilla (Amaicha del Valle, Tucumán, Argentina) is located. We start with an overview of the general attributes of the regional lithic resource base, followed by a characterization of the lithic raw materials used and, finally by a discussion of procurement quarries. More specifically, we discuss the usefulness of the tertiary source concept in relation to long-term use/exploitation of procurement sources.